Farmers' Motivation in Implementing Jajar Legowo Planting System in Tegalsari, Kepanjen, Malang - Hamyana; Khoirunisak; Ugik Romadi (Universitas Muhammadiyah Malang, 2022)
This study aims at determining the factors affecting the farmers' motivation in implementing Jajar Legowo planting system. This study was conducted in Tegalsari, Kepanjen, Malang, from April to June, 2020. The population in this study was the members of farmer groups